Zadanie 4
A. 3x + 5 = 4 + 2x +1
3x + 5 = 5 + 2x
3x - 2x = 5 - 5
x = 0
B. 2x - 2 + x = 3x - 1
3x - 2 = 3x - 1
3x - 3x = -1 + 2
0 = 1
C. 4x - 1 = 3(x + 1) + (x - 4)
4x - 1 = 3x + 3 + x - 4
4x - 1 = 4x - 1
4x - 4x = - 1 + 1
0 = 0
D. -6 + x = -x + 6
x + x = 6 + 6
2x = 12
x = 6
Odp.: C
Zadanie 5
Tutaj równania są takie same jak w zadaniu 4, więc z powyższych rozwiązań można wskazać równanie B
Zadanie 6
A. 3(x + 10) = -7x
3x + 30 = -7x
3x + 7x = -30
10x = -30 /:10
x = -3
B. 3(x + 10) = 3x - 2
3x + 30 = 3x - 2
3x - 3x = -2 -30
0 = -32
C. 3(x + 10) = 5
3x + 30 = 5
3x = 5 - 30
3x = -25 /:3
x = [tex]-8\frac{1}{3}[/tex]
D. 3(x + 10) = 6 - x
3x + 30 = 6 - x
3x + x = 6 - 30
4x = -24 /:4
x = -6
Odp.: A